Occurrence and Source Apportionment of Polycyclic Aromatic Hydrocarbons (PAHs) in Green Mussel (Perna viridis) from Cilincing Waters of Jakarta Bay, Indonesia - Deny Yogaswara; Tri Partono; Awalina Satya (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2021)
Green mussels (Perna viridis) as sedentary organisms have been adopted as bioindicators in the marine environment for many decades. They have been potentially affected by anthropogenic activity and organic contaminants such as polycyclic aromatic hydrocarbons (PAHs) in an aquatic environment. This study aims to determine concentration, distribution and potential sources of PAHs in green mussel biomass obtained from Cilincing waters, Jakarta Bay. Fresh green mussels were collected from aquaculture facilities at Cilincing waters of Jakarta Bay with various size categories of shell length and were extracted with solvent n-hexane-dichloromethane mixture using Soxhlet method. The concentrate of sample extract was purified using silica gel/sodium sulfate anhydrous with n-pentene-DCM effluent in fractionation. Finally, the purified sample was injected into the GC-MS instrument. The result showed that the highest concentration of total PAH (TPAH) was 126.47 ng.g-1 wet weight (ww), founded in the guts from the biggest group of green mussel (length of 6.00 to 7.99 cm), and     3-aromatic rings were predominantly detected in all group sizes of green mussel. The result of the   LMW/  HMW and diagnostic binary ratio indicated that PAH contamination is caused by a mixed source of petrogenic and pyrogenic processes. It may be due to the presence of oil spilled and petroleum waste from shipyard and cargo activities and atmospheric deposition. Based on excess cancer risk (ECR) value and the concentration level of PAH carcinogenic according to National Agency of Drug and Food Control (BPOM) regulation, PAH level in green mussels are acceptable and minor negative impact due to typical human consumption. Nevertheless, it needs to be circumspect to exploiting green mussels as seafood resources for daily consumption due to the carcinogenic content.